Enhanced vibrational energy harvester based on velocity amplification. (March 2014) - Cottone, Francesco; Frizzell, Ronan; Goyal, Suresh; Kelly, Gerard; Punch, Jeff
This article presents a fundamental investigation in which velocity amplification is employed in non-resonant structures to enhance the power harvested from ambient vibrations. Velocity amplification is achieved utilising sequential collisions between free-moving masses, and the final velocity is proportional to the number of masses and the mass ratios selected. The governing theory is discussed, particularly how the final velocity scales with the number of masses. This article examines n-mass velocity-amplified vibration energy harvesters and examines their performance relative to single-mass harvesters. Electromagnetic energy conversion is chosen as it is fundamental in allowing the free movement of the masses. Experimental results from two- and three-mass prototypes are presented that demonstrate a wider frequency response and a gain in power of 33 times compared to single-mass configurations under wideband random excitation. The volume of the devices was constrained, which resulted in the two-mass system outperforming the triple-mass system counter to expectations. This was caused by the triple-mass device experiencing an increased number of impact due to the volume constraint, leading to high losses in the system. It is recommended that in order to realise the full benefits of the triple-mass system, additional volume for mass actuation is required.